2021
DOI: 10.3390/coatings11121556
|View full text |Cite
|
Sign up to set email alerts
|

UV Curable Coatings Based on Urethane Acrylates Containing Eugenol and Evaluation of Their Antimicrobial Activity

Abstract: This work presents studies on the obtaining of UV-curable coatings with antimicrobial activity. Urethane acrylates (UAs) have excellent physicochemical properties including high reactivity in systems with radical photoinitiators in the presence of UV radiation and good balance between hardness and flexibility in the formed coatings. At the same time, eugenol is well known as the compound hindering the growth of various microorganisms. Hence, the materials obtained by the modification of UA resins with eugenol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Bednarczyk and coworkers used trimethylolpropane triacrylate (TMPTA) and eugenol to develop antimicrobial coating. Reactive diluent eugenol incorporated into the coating inhibited microorganism growth [110]. Lee and coworkers used isobornyl acrylate (IBOA) as a reactive diluent to develop UV coating [111], whereas Seo and coworkers used TMPTA as a reactive diluent to achieve coating with better chemical and mechanical properties [112].…”
Section: Uv Coating Technology Typesmentioning
confidence: 99%
“…Bednarczyk and coworkers used trimethylolpropane triacrylate (TMPTA) and eugenol to develop antimicrobial coating. Reactive diluent eugenol incorporated into the coating inhibited microorganism growth [110]. Lee and coworkers used isobornyl acrylate (IBOA) as a reactive diluent to develop UV coating [111], whereas Seo and coworkers used TMPTA as a reactive diluent to achieve coating with better chemical and mechanical properties [112].…”
Section: Uv Coating Technology Typesmentioning
confidence: 99%
“…They reported that an increase in TMPEOTA content results in an increase in the T g , storage modulus, and mechanical properties. Antibacterial UV-curable coatings based on the polyurethane acrylate using eugenol as a reactive diluent were studied by Bednarczyk et al, who studied the influence of the amount of eugenol on the chemical, physical, thermal, and mechanical properties [ 15 ]. Oh et al reported that cardanol-based acrylates as reactive diluents for UV-curable coatings.…”
Section: Introductionmentioning
confidence: 99%